Calling STEM experts: how can experts contribute to students' increased STEM engagement?. Issue 1 (2nd January 2017) - Gamse, Beth C.; Martinez, Alina; Bozzi, Laurie
ABSTRACT: Encouraging student interest in science, technology, engineering, and math (STEM) is an urgent priority in the USA and abroad. How most effectively to generate and sustain student interest in and preparation for STEM education and careers remains a vexing question, as the content areas, target ages, instructional approaches, and specific purposes of STEM education—and career preparation—are so diverse. Political interest in uncovering means to prepare and engage both larger numbers and more diverse students in STEM fields has extended to the practice of engaging STEM professionals in educational activities with students. What is the empirical evidence about which approaches that rely upon STEM experts to engage students work, and for whom? This paper summarizes research about the effects of such programmes on student outcomes, and offers recommendations for strengthening the research basis about using STEM professionals in the future.